2022
DOI: 10.1002/crat.202200008
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of One‐Step Synthesis of Oxides from Metal Chlorides and Their Electrocatalytic HER Study

Abstract: It is well known that a layered structure can improve charge transfer and is a favorable catalyst material. Most of them are metal oxides, and some metal hydroxides and carbonates have also been proved to have good catalytic performance. Generally, the preparation method is to prepare the precursor and then calcinate them to get metal oxides. Through literature review and repeated experiments, it is found that cationic membrane electrosynthesis with CeCl3·7H2O as a raw material may be able to prepare metal oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Under acidic conditions, hydrogen ions undergo reduction to form hydrogen, with the equilibrium half-cell potential being 0 V. Meanwhile, under alkaline conditions, water molecules are reduced to produce hydrogen and hydroxyl groups, resulting in an equilibrium half-cell potential of 0.83 V. The HER is a cathodic process involving a two-electron transfer. It has been observed that HER primarily follows either the Volmer-Tafel path or the Volmer-Heyrovsky path, as shown in Equations ( 1)-( 6) [140][141][142][143][144][145]. HER tends to occur via the Volmer-Tafel path or the Volmer-Heyrovsky path, given in Equations ( 1)-( 6).…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%
“…Under acidic conditions, hydrogen ions undergo reduction to form hydrogen, with the equilibrium half-cell potential being 0 V. Meanwhile, under alkaline conditions, water molecules are reduced to produce hydrogen and hydroxyl groups, resulting in an equilibrium half-cell potential of 0.83 V. The HER is a cathodic process involving a two-electron transfer. It has been observed that HER primarily follows either the Volmer-Tafel path or the Volmer-Heyrovsky path, as shown in Equations ( 1)-( 6) [140][141][142][143][144][145]. HER tends to occur via the Volmer-Tafel path or the Volmer-Heyrovsky path, given in Equations ( 1)-( 6).…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%